Pengaruh Beban Kerja Fisik dan Kualifikasi Karyawan terhadap Produktivitas Kerja Karyawan (Studi Kasus di PT. Bukaka Inti Aircon) - Jihad, Muhammad; Budiono, Nugrahadi Dwi Pasca (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Work productivity in the world and in Indonesia is still experiencing a downward trend, namely from (47%) in 1960 to (1%) since the beginning of 2000. Several factors influence work productivity, namely physical workload and employee qualifications. Therefore, the aim of this research is to analyze the influence of physical workload and employee qualifications on the work productivity of case study employees at PT. Bukaka Inti Aircon. This research method is quantitative with an analytical observational design cross sectional. The sampling technique uses simple random sampling, totaling 69 employees. The instrument of this research is a questionnaire, statistical test analysis using tests Logistic Regression. The results of this research showed that almost half of the employees experienced an inappropriate workload, namely (46.4%) and most of the employees were included in the incompetent category, namely (50.7%). Based on test results Logistic Regression shows that the physical workload variable has a significance of 0.004 which is smaller than 0.05 and employee qualifications have a significant impact on work productivity with a significance value of 0.031 which is smaller than 0.05. Conclusion There is a significant influence of physical workload and employee qualifications on employee work productivity at PT. Bukaka Inti Aircon, so that PT Bukaka Inti Aircon employee needs to make adjustments regarding excessive work duration and Overwork as well as readjusting employee qualifications both in terms of training and competency in each field so as to maintain good work productivity.